2013
DOI: 10.4254/wjh.v5.i9.487
|View full text |Cite
|
Sign up to set email alerts
|

Pure laparoscopic hepatectomy for hepatocellular carcinoma with chronic liver disease

Abstract: Pure laparoscopic hepatectomy is a less invasive procedure than conventional open hepatectomy for the resection of hepatic lesions. Increases in experiences with the technique, in combination with advances in technology, have promoted the popularity of pure laparoscopic hepatectomy. However, indications for usage and potential contraindications of the procedure remain unresolved. The characteristics and specific advantages of the procedure, especially for hepatocellular carcinoma (HCC) patients with chronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…At present, no concrete evidence exists for the recommendable treatment of CP-C HCC patients except for liver transplantation. However, we often experience cases in which treatment definitely prolongs survival, and there are several reports demonstrating the efficacy of treatments for CP-C HCC [12,13,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…At present, no concrete evidence exists for the recommendable treatment of CP-C HCC patients except for liver transplantation. However, we often experience cases in which treatment definitely prolongs survival, and there are several reports demonstrating the efficacy of treatments for CP-C HCC [12,13,14,15,16,17,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…41,42 Minor resections can be performed for ICG clearance rates of up to 22%, 43 limited hepatectomies (without sacrifice of non-tumorous liver) for values up to 40%, 23 and limited wedge laparoscopic resections can possibly be tolerated for even higher values. 44,45 Preoperative Portal Vein Embolization (PVE), first introduced by Makuuchi et al, 46 has been widely recognized as an effective method for the preoperative volume modulation of small FLR. However, the degree of hypertrophy of the FLR after PVE is variable in patients with CLD.…”
Section: Assessment and Modulation Of Remnant Liver Functionmentioning
confidence: 99%
“…62 The safety and feasibility of the laparoscopic approach and its short-term benefits for HCC patients with CLD have been demonstrated by many studies. 45 Tranchart et al 63 reported better postoperative outcomes, without long-or short-term oncologic consequences, following laparoscopic LR of HCC for select patients. Laparoscopic LR has the advantage of minimal ascites, 64 due to preservation of venous and lymphatic collateral circulation, which leads to lower risk of disturbance in water and/or electrolyte balance and hypoproteinemia that could trigger fatal liver failure.…”
Section: Laparoscopic Liver Resectionmentioning
confidence: 99%
“…Pure laparoscopic hepatectomy results in minimal postoperative ascites production, which leads to a lower risk of disturbance in water and/or electrolyte balance and hypoproteinemia. It leads to lower complications that could potentially lead to postoperative serious liver failure (44). In very little cases some authors suggest to perform the Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) for HCC.…”
Section: Laparoscopic Advantages and Future Perspectivesmentioning
confidence: 99%